(untitled) (Herald of Journalism, 2020)
The article discusses the practice of modernization, as a system of mass communication combines all the tools for collecting, analyzing, transmission, processing and dissemination of public information. Denote the components of the system. Details the specifics of each type of media. The results of sociological research. Reflected the general vector distribu- tion media preferences population main age groups (young, middle-aged, retired). The data presented in the article may serve as a guide to deter- mine the forms and methods of work of the press service with adult audi- ences and the media.